Assessment of walking disorder in community-dwelling Japanese middle-aged and elderly women using an inertial sensor - Miyashita,Toshinori; Kudo,Shintarou; Maekawa,Yoshihiro (PeerJ, 2021)
Background Decreased walking speed has been revealed to be related to many negative events. Several researchers support the importance of triceps surae function as a cause of decreased walking speed. The purpose of this study was to investigate the relationship between walking speed and plantar flexor power during the terminal stance of gait in community-dwelling middle-aged and elderly women using an inertial sensor. Methods One hundred thirty-six healthy female middle-aged to elderly community-dwelling women were included in this study. We measured two-step score, grip strength, walking speed and accelerometer data from which we estimated ankle power (estimated ankle power) during walking using an inertial sensor. All participants were classified into the four different age strata, fifties (50–59), sixties (60–69), seventies (70–79) and eighties (80–89). The differences in each parameter between the four age groups were compared using repeated analysis of variance and post-hoc Bonferroni corrections for multiple comparisons to establish significance. Multiple regression analysis was carried out using a stepwise method to determine the correlations with comfortable walking speed. Comfortable walking speed was considered a dependent variable. Results The normalized estimated ankle power of the eighties group was significantly decreased in comparison with seventies age groups and fifties age groups (P < 0.05), but there were no significant differences in normalized estimated ankle power between the sixties and eighties age-groups. The results of stepwise multiple regression analysis revealed that the normalized estimated ankle power, two-step value and body weight were highly-significant partial regression coefficients (adjusted R2 = 0.57).
Keywords: Inertial sensor; Ankle plantar flexor power; Walking speed; Middle-aged; Elderly; Walking assessment